1996
DOI: 10.1007/bf00140511
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural adaptation to climatic variation

Abstract: Assumptions tmderlying impact assessments of climatic change for a~iculture are explored conceptually and empirically. Variability in climatic conditions, the relevance of human decisionmaking, and the role of non-climatic forces are reviewed and captured in a model of agricultural adaptation to climate. An empirical analysis of farmers' decisions in light of variations in climate and other forces is based on a survey of 120 farm operators in southwestern Ontario. Many farmers were affected by variable climati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(112 citation statements)
references
References 26 publications
2
107
0
3
Order By: Relevance
“…Although agricultural productivity varies as a function of land use and management issues (Rounsevell et al, 1999), forecasting future agricultural yields requires explicit attention to climatic variability (Smit et al, 1996) and climatic conditions on spatial scales much smaller than those offered by the most highly resolved general circulation models (GCMs). Extended periods of high air temperature with below normal precipitation can cause moisture stress to agricultural crops, such as corn and soybeans, and negatively impact yields (Carlson, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Although agricultural productivity varies as a function of land use and management issues (Rounsevell et al, 1999), forecasting future agricultural yields requires explicit attention to climatic variability (Smit et al, 1996) and climatic conditions on spatial scales much smaller than those offered by the most highly resolved general circulation models (GCMs). Extended periods of high air temperature with below normal precipitation can cause moisture stress to agricultural crops, such as corn and soybeans, and negatively impact yields (Carlson, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…However, because governments have responded to past droughts with disaster relief packages, there may be little incentive for farmers to take defensive action themselves. This insulation against the effects of an anticipated extreme event could promote what Smit et al 44 describe as maladaptation to climate change. Such a situation actually took place in summer 1988, with an El Niño-induced drought requiring federal support payments (including crop insurance) in excess of $1.3 billion (Canadian), an amount further supplemented by provincial support programs.…”
Section: Moving Beyond Assumptions About Adaptabilitymentioning
confidence: 99%
“…In one study, an empirical analysis of 120 southwestern Ontario farmers, 44 it was found that although the majority of respondents reported being affected by variable climatic conditions over a 6-year study period, only one in five made any conscious effort to adjust their operations in light of climatic events. Similar findings are emerging from an ongoing study of agricultural adaptation to climate on a sample of farms in southern Alberta.…”
Section: Moving Beyond Assumptions About Adaptabilitymentioning
confidence: 99%
“…Small holder farmers have in many years been depended on favourable rainfall patterns for a good yield in Zimbabwe. Farming communities do not only respond to rainfall quantity, but also to variations in time, as a result, the relatively small changes in rainfall frequency may have strong effects on communities [1][2][3]. The farmers mostly practise rain-fed crop farming with a handful irrigating as this situation is driven by lack of resources and funds to have the irrigation infrastructure.…”
Section: Introductionmentioning
confidence: 99%